Answer:
The solution for system of equations 3x + y = -5; x + 4y = 2 is x = -2 and y = 1
Solution:
With the help of substitution method of algebraic equations,
3x + y = - 5 -------------- equation 1
x + 4y = 2 --------------- equation 2
Multiplying equation 1 by 4, equation 1 can be rewritten as
12x + 4y = -20 ------------- equation 3
Multiplying equation 2 by -1, equation 2 can be rewritten as,
- x - 4y = -2 ----------------- equation 4
Solving equation 3 and 4, we get
12x + 4y = -20
-x - 4y = -2
11x = -22
x = -2
Substitute x = -2 in equation 2
-2 + 4y = 2
4y = 4
y = 1
hence we obtain x = -2 and y = 1